A short review about some exotic systems containing electrons, muons, and tauons - Press Authors, OICC (Journal of Theoretical and Applied Physics, 2023)
AbstractSome remarks about exotic systems consisting of various masses of fermions and antifermions have been presented. In paricular, few body systems containing electrons, muons and tauons, and the fundamental interest of the study of their bound states systems have been discussed.